Long-Term Outcomes (2 Years) After Hyaluronic Acid Therapy for Peyronie’s Disease - Cocci, Andrea; Di Mauro, Marina; Kluth, Luis; Capogrosso, Paolo; Falcone, Marco; Mondaini, Nicola; Russo, Giorgio Ivan (Frontiers in Urology, 2022)
Background Hyaluronic acid (HA) has demonstrated clinical benefits for the treatment of Peyronie’s disease (PD); however, there are no reports that documented long-term outcomes. The aim of the current study is to illustrate the clinical outcomes after 2 years of follow-up in patients who received HA for PD. Methods From January 2015 to December 2018, we enrolled 244 patients affected by PD in this multicenter non-randomized clinical study, as previously reported. Patients received intralesional HA (Group A) or verapamil (Group B). Follow-up was undertaken after 3 months, 1 year, and 2 years. International Index of Erectile Function (IIEF-5), PC, and visual analogue scale (VAS) were collected. Results Among the whole cohort, 125 patients were included in Group A and 119 in Group B. As PC, the median curvature was 25.0° at 3 months [interquartile range (IQR), 15.0–30.0] (p=0.45) and was maintained at 1 (p=0.87) and 2 years of follow-up (p=0.90) (Group A), while it was 30.0° (IQR, 20.0–35.0) (p=0.67) at 3 months and was stable at 1 (p=0.77) and 2 years of follow-up (p=0.80) (Group B). For VAS score, the median change in Group A was −4.0 (IQR, −4.0, −5.0, p<0.01) after 3 months, −4.0 (IQR, −4.0, −5.0, p<0.01) at 1 year, and −4.0 (IQR, −4.0, −5.0, p<0.01) at 2 years of follow-up, while in Group B, it was −1.0 (IQR, −2.0, −0.5, p=0.25) after 3 months, −3.5 (IQR, −3.5, −2.0, p<0.01) at 1 year, and −4.0 (IQR, −4.0, −5.0, p<0.01) at 2 years of follow-up. Adjusted p-value for between-group comparisons was <0.01 at 3 months and not significant at 1 (p=0.53) and 2 years (p=0.80). Conclusions We reported clinical efficacy of intralesional HA in patients with PD after 2 years of follow-up by slightly improving penile curvature (PC) and bother of the disease. These results should be considered during the counseling of the patients especially regarding the lack of worsening over time.